Low molecular weight heparins in cancer patients: to treat thromboembolic events, the tumor, or both? - Sergio Siragusa (Frontiers Media S.A., 2011)
The interrelationship between cancer and thrombosis is well known. Recent data help physicians to optimize the management of thrombotic complications occurring in cancer patients. However, many issues are still uncertain. First, although the development of venous thromboembolism (VTE) in a patient with known cancer is the most common presentation, concerns remain about the optimal duration and dosages of anticoagulants. Questions also arise concerning the need to implement heparin prophylaxis in the course of chemotherapy. Secondly, in some patients, thrombosis precedes the diagnosis of malignancy. In this case, the question is whether or not to screen patients for an occult cancer. Thirdly, very recent studies have shown the hemostatic system plays a key role at different stages of tumor growth. Anticoagulants, especially low molecular weight heparin (LMWH), appear therefore to be an attractive strategy not only for managing the risk for thrombosis but, possibly, to improve patient outcome and survival. However, the use of these compounds in settings other than VTE is questionable. Finally, most of the data come from studies evaluating patients with different types of cancer at different stages, thus making results difficult to evaluate. Additional research is required to clarify the biological mechanisms involved and to answer still unresolved clinical questions. In this review, the evidence for the use of LMWHs in cancer patients will be presented and remaining doubts discussed.